2023
DOI: 10.1038/s41467-023-37865-3
|View full text |Cite
|
Sign up to set email alerts
|

Low complexity domains of the nucleocapsid protein of SARS-CoV-2 form amyloid fibrils

Abstract: The self-assembly of the Nucleocapsid protein (NCAP) of SARS-CoV-2 is crucial for its function. Computational analysis of the amino acid sequence of NCAP reveals low-complexity domains (LCDs) akin to LCDs in other proteins known to self-assemble as phase separation droplets and amyloid fibrils. Previous reports have described NCAP’s propensity to phase-separate. Here we show that the central LCD of NCAP is capable of both, phase separation and amyloid formation. Within this central LCD we identified three adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 93 publications
0
25
0
Order By: Relevance
“…481 Apart from cancer, lethal viral infections such as SARS-CoV-2 (the severe acute respiratory syndrome coronavirus 2) have also shown its potential connection with LLPS and amyloid aggregation as the nucleocapsid protein of the virus contains LCD promoting both events. 482,483 Similarly, a metabolic disorder such as type II diabetes has also been shown to be affected by LLPS-mediated aberrant aggregation as insulin-derived peptides and islet amyloid polypeptide (IAPP) can promote the amyloidogenic pathway from phase separation. 484,485 Since the LLPS phenomenon is ubiquitous in cell physiology, the underlying pathological risk of cellular mis-regulation is an unavoidable consequence leading to diverse disease pathogenesis.…”
Section: Llps: a Generic Nucleation Mechanism In The Amyloid Aggregat...mentioning
confidence: 99%
“…481 Apart from cancer, lethal viral infections such as SARS-CoV-2 (the severe acute respiratory syndrome coronavirus 2) have also shown its potential connection with LLPS and amyloid aggregation as the nucleocapsid protein of the virus contains LCD promoting both events. 482,483 Similarly, a metabolic disorder such as type II diabetes has also been shown to be affected by LLPS-mediated aberrant aggregation as insulin-derived peptides and islet amyloid polypeptide (IAPP) can promote the amyloidogenic pathway from phase separation. 484,485 Since the LLPS phenomenon is ubiquitous in cell physiology, the underlying pathological risk of cellular mis-regulation is an unavoidable consequence leading to diverse disease pathogenesis.…”
Section: Llps: a Generic Nucleation Mechanism In The Amyloid Aggregat...mentioning
confidence: 99%
“…NP consists of two structured domains, the N-terminal domain (NTD), and the C-terminal domain (CTD), which are connected by a linker. The CTD serves as a dimerization domain of NP, which in turn has also been reported to form higher order oligomers via its linker region (17), as well as via its C-terminal helix (18). Many previous studies have demonstrated the importance of NTD in association with viral RNA and described the atomic details of these interactions (19).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently discovered that the SARS-CoV-2 virus proteome includes different sequences of amyloid-forming proteins [ 4 , 29 , 30 ]. It is assumed that amyloid-forming proteins from the SARS-CoV-2 virus may be involved in the development of neurological symptoms in COVID-19-infected patients [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%